Revitalisasi Ritual Sampang Sandro Sebagai Daya Tarik Wisata - Sarumaha, Petra Selsia Krisnawati; Anom Kumbara, A.A Ngr (Humanis; Vol 24 No 1 (2020)DO - 10.24843/JH.2020.v24.i01.p07, 2020)
This study discusses about Gili Indah village which has a sampang sandro ritual . l ately this ritual is almost extinct because the activity as a salt farmer did not ensure in society's economy, so they switch to other professions. Those switching profession indirectly causes the loss of unique ritual of that. L ocal government are trying to revitalize sampang sandro ritual to used as an alternative tourist attraction. Based on the background study above, this study focus on (1) How are the revitalization of sampang sandro ritual in Gili Indah village? (2) How the implication of revitalization of sampang sandro ritual for society in Gili Indah village?. Furthermore, the method of data collection in this study are observation, interview, and documentation method. The data were analysed in qualitative with functionalism and the change of social theories. The results of this study were showed that sampang sandro ritual was done in festival ritual of sampang sandro . F irst step is competition of gangsing (mangkeq), kasti ball, pantok cret, dayung kano, and photography. Sampang Sandro is point event with some procession such pray, chicken release, take salt in the swamp, lunch together then cleaning up. The implication of revitalization of sampang sandro ritual are the maintenance of local tradition and preservation of social solidarity. Then, the implication in ecology field is preservation of ecosystem sustainability. The implication in economy field is the increased of treasury village, and implication tourism field is the increased of tourist attractions in Gili Indah village.